2009
DOI: 10.1245/s10434-009-0762-4
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Resectability and Survival After Concurrent Chemoradiation in Primarily Unresectable Pancreatic Cancer

Abstract: The finding of a high proportion of R0 resection among all resections performed confirms the activity of neoadjuvant radiochemotherapy and should not be neglected. Based on these data, patients with unresectable pancreatic cancer without disease progression after chemoradiotherapy should be considered for radical surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
97
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 56 publications
5
97
1
5
Order By: Relevance
“…In fact, in our previous pilot study, a dose of 30 Gy in 10 fractions (3 Gy/fraction; EQD 2 : 32.5 Gy) produced a complete response of pain in 50% of patients with a partial response in a further 25% of patients. 27 Finally, the administration of a higher dose (37.5 Gy, 7.5 Gy/fraction, EQD 2 : 54.7 Gy with ˛/ˇ ratio of 10) to part of the tumor could increase the palliative effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, in our previous pilot study, a dose of 30 Gy in 10 fractions (3 Gy/fraction; EQD 2 : 32.5 Gy) produced a complete response of pain in 50% of patients with a partial response in a further 25% of patients. 27 Finally, the administration of a higher dose (37.5 Gy, 7.5 Gy/fraction, EQD 2 : 54.7 Gy with ˛/ˇ ratio of 10) to part of the tumor could increase the palliative effect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this dose is definitely higher compared to standard preoperative treatment of locally advanced pancreatic tumors (median: 50.2 Gy, range: 45-55.8 Gy). 27 Based on these results, prospective trials based on a clinical application of this strategy seem to be justified, at least in selected patients without overlapping between PTVd and PTVv, to evaluate the clinical efficacy of this technique in the setting of locally advanced pancreatic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An estimated 48,960 new cases of pancreatic cancer and 40,560 mortalities from pancreatic cancer occurred in the United States of America in 2015, making this cancer type the fourth leading cause of cancer-associated mortality (2). Surgery is the only reported cure for pancreatic cancer; however, the resectability rate is only 18% due to its high rate of vascular invasion and metastasis (3). Radiotherapy and chemotherapy may extend survival time to some extent, but their overall effectiveness remains limited (4).…”
Section: Introductionmentioning
confidence: 99%
“…Neoadjuvant treatment in the form of chemotherapy and/or radiation therapy is being used more frequently to downstage locally advanced unresectable lesions (28)(29)(30). Studies evaluating the impact of neoadjuvant chemo radiation have demonstrated that secondary resection becomes possible in about 30-40% of patients with locally SMA and SMV 2 [4] Celiac or portal lymphadenopathy 5 [10] Other/unknown 5 [10] Initial operation type, n [%]…”
Section: Discussionmentioning
confidence: 99%